Analisis Implikasi Kebijakan Dividen Terhadap Pertumbuhan Perusahaan Dan Kinerja Saham Studi Kasus Pada Pt Mitra Pinasthika Mustika Tbk Yang Terdaftar Di Bursa Efek Indonesia - Andre, Andre; Marpaung, Annaria Magdalena; Mekaniwati, Ani (Jurnal Ilmiah Manajemen Kesatuan, 2019)
This research was conducted using financial reports from companies engaged in retail distribution sector during the periods of 2013-2016 using financial ratios analysis. These ratios described how profitability, assets management and company’s equity are affecting the dividend policy. We can conclude that dividend policy has major impact on the company’s growth and stock performance. The results show that a slight decrease in the stock price will also cause a decrease in the profit and eventually causing decrease to the earning per share. The dividend per share experiences an increase because these companies still intent to pay the dividend among their share holders to maintain share price. Share price declines due to the interest rate policies of Bank Indonesia and the value of export import. These companies have run proper dividend policies by maintaining the growth and company value, seen from the increasing portion of retained earnings and the portion of dividend payment. Thus the decreasing price of share is mostly caused by external factors.